(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2016)
The use of English has become increasingly dynamic with the creation and expansion of new international networks of communication and the ubiquity of new technologies in and beyond the English-speaking world. This paper highlights the deficiencies of traditional Communicative Approach to foreign language teaching in Ukraine, and emphasizes the necessity to employ new educational technologies which are more efficient for teaching English as an international language, particularly in the academic sphere.